Portugal's Footwear Industry: Looking for Sustainability Practices - Duarte de Almeida, I.; da Silva, Agostinho (The 30th EurOMA Conference: A Systems Lens on Operations, 2023)
Fashion is a significant contributor to pollution and the footwear industry (FWi) is a culprit. Nevertheless, FWi is committed to sustainability looking for innovation, sustainable materials, new designs and new business models. However, sustainable design is challenging due to the diversity of materials and styles; finding options for synthetic rubber, genetically modified cotton, chromium-tanned leather, and chemical glues is stiff. This study adopts a qualitative research approach to building theory. A field study was conducted at 14 FW companies. We found that sustainable value is important in the vision and management of these companies. Some, looking for sustainable practices, have a circular economy (CE) approach. Creating sustainable value is a significant challenge for these companies due to the variety of natural and synthetic materials and the need for suitable technology to reduce waste and preserve natural resources. This study identifies the barriers and drivers for implementing sustainable practices in FWi.